Supplementary oxygen in healthy subjects and those with COPD increases oxidative stress and airway inflammation - Carpagnano, G (BMJ Group, 2004)
Background: Hyperoxia increases oxidative stress through the generation of reactive oxygen species and may therefore enhance inflammation in the lungs. The aim of this study was to investigate whether short term supplementary oxygen (28%) increases oxidative stress and inflammation in the airways by measuring 8-isoprostane and interleukin 6 (IL-6) concentrations in exhaled breath condensate. Methods: Twenty three healthy subjects (12 men, mean (SD) age 48 (7) years) and 23 patients with chronic obstructive pulmonary disease (COPD; 15 men, mean (SD) age 56 (5) years) were studied. 8-isoprostane and IL-6 concentrations were measured by immunoassay. Results: Increased concentrations of 8-isoprostane and IL-6 were found in all subjects after breathing 28% oxygen for 1 hour. In healthy subjects the concentrations of 8-isoprostane and IL-6 were 10.9 (2.9) pg/ml and 4.9 (0.8) pg/ml, respectively, compared with baseline concentrations of 6.1 (1.3) pg/ml and 2.9 (0.6) pg/ml, and in patients with COPD the concentrations were 27.9 (3.1) pg/ml and 8.3 (1.2) pg/ml), respectively, compared with baseline concentrations of 18.9 (3.6) pg/ml and 6.3 (0.6) pg/ml. By contrast, breathing air through the same face mask for 1 hour had no significant effects on 8-isoprostane or IL-6 concentrations in normal subjects or those with COPD. Conclusions: These findings suggest that short term supplementary oxygen may enhance oxidative stress and inflammation in the airways. Whether this happens with long term oxygen therapy needs to be determined.